Recalibration of perceived agency transfers across modalities - Belkis Ezgi Arikan; Kielan Yarrow; Katja Fiehler (Royal Society Open Science)
We experience our actions and their sensory consequences as synchronous despite small sensorimotor delays. This is attained by an adaptation process in which the sensorimotor system recalibrates temporal discrepancies between actions and their feedback, as long as causality is maintained (i.e. feedback follows action). Predictive motor mechanisms boost action–feedback binding, aiding in adaptation. Sensorimotor temporal recalibration is therefore closely linked with perceived control over the action and its sensory feedback (sense of agency, SoA). Interestingly, recalibration can also transfer to another sense, indicating a generalized mechanism that adjusts the timing of action–feedback events. It is unclear whether recalibration of perceived agency is driven by a similar mechanism. Here, we investigated cross-modal transfer of perceived agency and simultaneity in a sensorimotor recalibration task. In an adaptation phase, participants executed button presses leading to an immediate or lagged (150 ms) occurrence of a Gabor patch. Subsequently, they were asked to make simultaneity or agency judgements for action–feedback pairs (Gabor patch or tone) with variable response–stimulus asynchronies (RSAs). We found adaptation of synchrony and agency judgements with transfer of recalibration for agency judgements. Our findings suggest flexible recalibration of perceived agency, suggesting SoA is not inferred solely on a match with modality-specific motor predictions.